La sobreprotección infantil y su incidencia en el desarrollo conductual en niños de 4 a 5 años - Ortega León, Jessica Fernanda (2022)
In the present titling work, child overprotection and its impact on behavioral development in children aged 4 to 5 years were addressed as a central problem. The objective of the research was to identify the incidence of child overprotection in behavioral development in a positive way that allows autonomy in children from 4 to 5 years of initial level 2 in the Sigchos Millennium Educational Unit. The applied methodology was framed in the post positivist paradigm, of mixed approach, explanatory and applied type, of experimental and longitudinal design, through the application of the interview techniques to the teacher and the educational psychologist, the survey to the parents and the observation sheet for children in Initial Education. With this, the observation of negative behaviors in infants that are interrelated with an overprotective parenting style, such as insecurity, shyness, aggressiveness and lack of values, due to the excessive care and protection that the parents of children, was obtained. family provide at home. Therefore, we proceeded with the design and application of a training proposal for parents, through didactic activities, dynamics and technological resources, so that they recognize family overprotection and its effects on the development of behavior, with which, It has been possible to considerably reduce the negative effects of overprotection on children's behavior.